The effect of the family on educational attainment Among students of Islamic high schools - Yas , Abdel Moneim (Islamic Sciences Journal, 2023)
After the Basmalah and Dedication, the Word of Gratitude and Appreciation, and the Index of Contents, I Started with the Introduction and Showed in it that the Family and the School are the two most Important Educational Institutions in Society, and then I Spoke About the Research Plan in Which I Divided the Research into five Chapters: In the first Chapter, what is the Effect of the Family on Educational Achievement of Islamic high School Students. As for the Research Objectives, it is to Identify the Role of the Family in the Educational Process in Order to Raise the Level of Educational Attainment. As for the Second Chapter, which is the Theoretical Framework, I Divided it into two Topics, the first Being the Family, the Second in which I talked about the importance of the family and its impact, and the third in which I Explained the functions of the family. The second topic is academic achievement As for the third chapter, I divided it into two topics, the first showed the Factors affecting educational attainment, the second showed the role of parents in academic achievement, and after that I wrote the conclusion, and the fourth chapter mentioned the research community and sample, and the conclusion included presenting the results and their interpretation, recommendations and proposals, then I mentioned the sources and references, then I attached an appendix to one number, Which is the form of the questionnaire, and in conclusion I came out with some recommendations that I explained at the end of the research.